Socio-economic factors and family size in Odukpani Local Government, Cross River State, Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The study examines the effect of socio-economic conditions on family size in Odukpani Local Government Area of Cross River State, Nigeria. The general objective was to find out the effect of socio-economic crisis on family size. The research problems were clearly defined, specific research question was developed the research hypothesis was also formulated to guide the researcher in the investigation. Relevant literature was reviewed and theories were used to back the explication of the study. To achieve the objectives of the study survey researchdesign was employed, the purposive and stratified sampling technique was used to select respondents in the study area. A structured questionnaire was also constructed and administered to two hundred (200) respondents. Chisquare (X2) was used in analyzing the data retrieved. The results showed that, there is a significant relationship between socio-economic conditions and family size in Odukpani Local Government Area, Cross River State, there is a significant relationship between educational level and family size in Odukpani Local Government Area, Cross River State. Based on the findings; it was therefore, recommended that; the government in the collaboration withsocial welfare agencies as well as NGOs should formulate policies and develop programmes with the aim of sensitizing the general public on the need for family planning, so as to reduce the issues in family size.
Keywords: Socio-economic conditions; Family size; Educational level; Family planning